PENGARUH INDEPENDENSI DAN EFIKASI DIRI TERHADAP KINERJA AUDITOR (STUDI PADA KANTOR INSPEKTORAT KOTA KENDARI) - Tamburaka, Sulvariani; Marianti, Marianti (JURNAL AKUNTANSI DAN KEUANGAN, 2016)
Â ABSTRACTThe aim of the study was to examine the effect of independence and self efficacy to auditorâs performance at Inspectorate of Kendari City. The analysis technique used is multiple linear regression.The results showed that independence significantly affects the auditor performance. This is because preparation of the audit program free from the others influence, the audit implementation directly free to access resources, and the reporting free from any influences to modify all the fact. It means that the higher auditor independence, the better auditor performance will be achieved. Self efficacy affects the auditor performance but not significant. This is because the respondent perception that not really sure can finish the audit task better than the others. It means that self efficacy gave a positive contribution but not significant for auditor performance improvement.Keywords: independence, self efficacy, auditor performance